The Impact of the Decent Housing Assistance Program (RTLH) on the Welfare Level of the Community in West Aceh District - Anzalita, Livia; Sani, Sri Rosmiati; Shifa, Mutiara (The Future of Education Journal, 2025)
This study aims to analyze the impact of the Decent Housing Assistance Program (RTLH) on the welfare level of the community in West Aceh District. Using a quantitative approach and multiple linear regression method, this research examines the effect of the variables of Providing Ease and Licensing, Provision of Infrastructure, Facilities, and Public Utilities, Initiating Land Banking, and the Establishment of Zones for Prosperous Housing on community welfare. The analysis results show that the variables of Providing Ease and Licensing and Provision of Infrastructure, Facilities, and Public Utilities have a significant impact on community welfare in partial tests, while the variables of Initiating Land Banking and Establishing Zones do not have a significant partial effect. However, simultaneously, all four variables have a significant impact on community welfare with a coefficient of determination of 61.4%. These findings indicate the importance of synergy among various aspects of the RTLH program to improve community welfare and the need to optimize policies related to infrastructure, administrative ease, and more strategic housing planning.